Implementasi Pembelajaran Berbasis Sikap Ilmiah dan Keterampilan Proses Sains: Bagaimana Respon Mahasiswa Rumpun Non-Sains? - Syazali, Muhammad; Erfan, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2023)
Learning based on scientific attitudes and scientific process skills is common among science students. However, this learning is almost never applied to non-science students, especially Primary School Teacher Education (PGSD) students at Mataram University. The aim of this research is to describe student responses to the implementation of learning based on these two aspects of science. This descriptive research using the survey method was carried out on PGSD students who were taking Basic Natural Sciences (IKD) courses in the odd semester of the 2021-2022 Academic Year. The sample consisted of 167 students who were determined using the purposive sampling method. Response data on learning implementation was measured using a questionnaire instrument which was distributed to respondents via a link in the Google Form application. Based on the survey results, we found that 53.3% of students stated that they had studied science through the research process, and the results were written in the form of scientific papers. As for the impression, the response from all students was positive. The details were 17.4% felt very happy, 53.3% were happy, and the remaining 29.3% answered quite happy. This is encouraged because they benefit from learning based on process skills and scientific attitudes. However, there are still 15.6% of students who experience difficulties in the process. The cause is the obstacles experienced by most of them (87.4%), and there are also students (6%) who feel that the time given is not enough. Some of the difficulties experienced by students include finding research problems (25.1%), formulating titles (26.9%), designing research activities (18%), and collecting data (29.9%). When writing scientific papers, the greatest difficulty lies in writing results and discussion (63.5%), followed by writing research methods (19.8), and the rest is in writing the abstract, introduction, conclusion and bibliography. The sample paper media used can help students in writing papers, but as many as 95.2% of students need additional facilities to practice their writing skills.